Representasi Komunikasi Forensik pada Film Ice Cold - Rena Lela Putri; Septiawan Santana Kurnia (UNISBA Press, 2024)
Abstract. The murder case of Mirna Salihin, which sparked controversy and inspired the making of the documentary film